LEGAL PROTECTION OF OWNERSHIP CERTIFICATE HOLDERS AGAINST THE VALIDITY OF LAND CERTIFICATES IN A NEGATIVE PUBLICATION SYSTEM - Marcelina, Nhelly; Wardhani, Novea Elysa; Evi; Istani (Pena Cendekia Insani, 2026)
This study aims to analyze the legal status and evidentiary strength of the Land Ownership Statement (SKT) in relation to the Certificate of Ownership (SHM), as well as the legal protection and certainty afforded to certificate holders. The research employs normative legal research methods using statutory, conceptual, and case approaches. The findings indicate that the SKT merely functions as an administrative basis of title, whereas the Certificate of Ownership constitutes a strong form of evidence of land rights, although it is not absolute under the negative publication system and may still be challenged if juridical or administrative defects are proven. The main issue addressed in this study is the lack of clear regulation regarding the legal status and limits of the evidentiary value of the SKT vis-à-vis the Certificate of Ownership. This study concludes that the land registration system based on negative publication has not yet fully ensured legal certainty and protection for holders of Certificates of Ownership, thus necessitating clearer regulation of the legal standing of the SKT and the strengthening of the land registration system.